Detection of Biological Contamination in Drinking Water Tanks and Sediments in some Areas of Mosul - Muthana Waad Mohammad, Mohammad Ibrahim Khalil, Ghaidaa Salah Hussein, (Pakistan Journal of Medical & Health Sciences, 2022)
This study was conducted in 10 selected areas, three on the east side of Mousl city, three on the west side of the City and four areas in Badoush which affiliated to the center of Mousl. Some physical and chemical tests were performed on water samples, such as pH and electrical conductivity, because of their importance and their impact on the properties of water. The results showed that the values of pH ranged between ( 7.5 – 8.4 ), the electrical conductivity values between ( 263.3 – 392.4 ) µs/cm, The results of biological tests also showed the presence of small number of unsatisfactory TPC bacteria in all samples while no numbers of fecal coliform bacteria or any other pathogenic bacteria appeared, some types of fungi also appeared in 7 samples, one sample had a type of yeast and tow samples were free of fungi and yeast.The results were within the permissible limits according to Iraqi or international standard, as for the fungi and yeast that appeared in the samples there are no determinations about them in the Iraqi and international specifications. Keywords: drinking water tanks, fungi, fecal coliform bacteria, biological contamination.